Microtexture porous multilayer structure composite current collector and preparation method thereof
By adopting a microtextured porous multi-layer structure in the current collector, combining porous polymer film, electroless metal layer, microtextured metal copper layer and corrosion-resistant lithium-resistant layer, the corrosion-resistant and lithium-resistant current collector is solved. The problem of dendrites overgrowth and slow charging rates achieves higher energy density and faster charging rates.
Patent Information
- Application Number
- CN202411850202.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-21
AI Technical Summary
The negative current collector for solid-state batteries faces problems such as corrosion, overgrowth of lithium dendrites and slow charging rate.
The microtextured porous multi-layer structure is used to combine the liquid collector, including a porous polymer film, an electroless metal layer, a microtextured metal copper layer and a corrosion-resistant lithium-philic layer, and the performance of the current collector is improved through these hierarchical structures and materials combinations.
It improves the surface area and corrosion resistance of the current collector, inhibits the abnormal growth of lithium dendrites, increases the charge and discharge current and charging rate, and meets the high energy density and low cost needs of lithium-ion batteries.
Smart Images

Figure CN119495752A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a micro-textured porous multi-layer composite current collector and a preparation method thereof. Background Art
[0002] As an efficient and environmentally friendly energy storage device, lithium-ion batteries are gradually becoming an important part of the future energy field. In the future, the important development directions of lithium-ion battery technology are mainly: high safety, high energy density and low cost. In order to achieve this goal, researchers are continuously exploring new battery materials and structural designs to promote the further development of lithium-ion battery technology. In a variety of new battery technology fields, the research of lithium-free negative electrode batteries, especially solid-state lithium-free negative electrode batteries, has become an important frontier to break through battery life anxiety and safety hazards. Compared with traditional lithium-ion batteries, lithium-free negative electrode batteries directly plate the limited lithium source from the cathode to the current collector during the charging and discharging process, which puts forward new requirements for the current collector material, mainly including: (1) high electronic conductivity and low resistance; (2) excellent chemical and electrochemical stability, which can resist the corrosion and side reactions of electrolytes, especially sulfide system electrolytes; (3) excellent mechanical strength; (4) lower lithium compound binding energy, which is conducive to the nucleation of lithium ions and inhibiting the transitional growth of lithium dendrites; (5) lower metal resource consumption.
[0003] To meet the requirements of lithium-free negative electrode batteries for current collector materials, researchers tested lithium deposition on a series of metal substrates and found that the substrate with the largest crystal mismatch with lithium metal exhibited the highest nucleation overpotential. Metallic lithium has a body-centered cubic (BCC) crystal structure and is therefore advantageously deposited on substrates with a BCC structure. In addition, lithium is also advantageously deposited on lithiophilic materials that are partially solubilized or alloyed with lithium metal. Related research provides support for the development of the existing electrolytic copper foil as the mainstream current collector material. Secondly, to achieve higher energy density and faster charging rate, there are several possible methods for current collector design, mainly including: (1) completely replacing copper as the current collector; (2) coating a modified layer on copper; (3) porous structure.
[0004] At the same time, in view of the problems of corrosion, excessive growth of lithium dendrites and slow charging rate faced by negative electrode current collectors in existing battery technologies such as silicon-carbon negative electrode batteries and solid-state batteries, there is an urgent need to develop new current collector technologies for high-performance batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a micro-textured porous multi-layer structure composite current collector and a preparation method thereof, so as to solve the problems of corrosion, excessive growth of lithium dendrites and slow charging rate faced by negative electrode current collectors for solid-state batteries.
[0006] The present invention adopts the following technical scheme: a micro-textured porous multi-layer composite current collector, comprising: a porous polymer film in the middle, chemically plated metal layers on both sides of the porous polymer film, a micro-textured metal copper layer on the outside of the two chemically plated metal layers, and a corrosion-resistant lithium-philic layer on the outside of the two micro-textured metal copper layers;
[0007] The two chemically plated metal layers, the micro-textured metal copper layer, and the corrosion-resistant lithium-philic layer are uniformly deposited on the inner surface and the outer surface of the pores of the porous polymer membrane in sequence;
[0008] The porous polymer film has a thickness of 4 to 13 μm, a pore size of 1.5 to 30 μm, and a porosity of 30 to 60%.
[0009] The composite current collector has a thickness of 5.2 to 15 μm, a pore size of 1.7 to 28 μm, and a porosity of 25 to 45%.
[0010] The composite current collector has protruding textures attached to the inner and outer surfaces of the holes; the particle size of the protruding textures is 0.05-0.1 μm;
[0011] The composite current collector has a tensile strength of ≥200 MPa, an elongation of ≥10%, and a resistivity of ≤20 mΩ.
[0012] Furthermore, the porous polymer film is a PET film, a PE film, a PP film or a PSF film.
[0013] Furthermore, the chemically plated metal layer is a copper, nickel or copper-nickel layer.
[0014] Furthermore, the corrosion-resistant lithium-philic layer is Ni-B, Ni-Sn, Ni-Zn, Ni-Ag or Ni-Graphite.
[0015] A method for preparing a micro-textured porous multi-layer structure composite current collector comprises: using a porous polymer film as a template of the composite current collector, depositing chemically plated metal layers on both sides thereof, plating the chemically plated metal layers on the outer side of the porous polymer film by means of colloidal palladium or colloidal copper catalyst during deposition, and then preparing a micro-textured metal copper layer and a corrosion-resistant lithium-philic layer by means of electroplating.
[0016] The beneficial effects of the present invention are:
[0017] The present invention increases the surface area of the current collector by providing a porous polymer film and a micro-textured metal copper layer, which not only increases the charge and discharge current, but also plays a role in inhibiting the abnormal growth of lithium dendrites; metallization of the outer surface of the porous polymer film is achieved by providing a chemically plated metal layer, thereby achieving low-cost and high-yield metallization; corrosion-resistant lithium-affinity layers are provided to improve the corrosion resistance and lithium-affinity of the current collector, meet the corrosion resistance requirements of lithium-ion batteries represented by sulfide solid-state batteries, and play a role in promoting the nucleation of lithium dendrites and inhibiting the abnormal growth of lithium dendrites;
[0018] The composite current collector prepared by the present invention has a large surface area and is more corrosion-resistant; compared with electrolytic copper foil or composite copper foil current collector, it has a larger interface contact area and better corrosion resistance;
[0019] The composite current collector preparation method of the present invention has many advantages such as low equipment investment, low production cost, and high product yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a schematic diagram of a composite current collector according to Example 1 of the present invention;
[0021] Figure 2 This is a backlight image of the composite current collector of Example 1 of the present invention;
[0022] Figure 3 This is a cross-sectional microstructure diagram of the composite current collector of Example 1 of the present invention;
[0023] Figure 4 This is a surface morphology image of the composite current collector of Example 1 of the present invention;
[0024] Figure 5 This is a morphology diagram of the pores of the composite current collector of Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] The present invention discloses a micro-textured porous multi-layer composite current collector, such as Figure 1 As shown, it includes: a porous polymer membrane located in the middle, chemically plated metal layers located on both sides of the porous polymer membrane, micro-textured metal copper layers located outside the two chemically plated metal layers, and corrosion-resistant lithium-philic layers located outside the two micro-textured metal copper layers.
[0027] The two chemically plated metal layers, the micro-textured metal copper layer, and the corrosion-resistant lithium-philic layer are uniformly deposited on the inner surface and the outer surface of the pores of the porous polymer membrane in sequence; the thickness of the porous polymer membrane is 4-13 μm; the pore size is 3-30 μm; the porosity is 30-60%; the thickness of the composite current collector is 5.2-15 μm, the pore size is 1.7-28 μm; the porosity is 25-45%; the inner surface and the outer surface of the pores of the composite current collector are attached with raised textures; the particle size of the raised texture is 0.05-0.1 μm; the tensile strength of the composite current collector is ≥200 MPa; the elongation is ≥10%; and the resistivity is ≤20 mΩ.
[0028] Wherein, the porous polymer film is a PET film, a PE film, a PP film or a PSF film.
[0029] Wherein, the chemically plated metal layer is a copper, nickel or copper-nickel layer.
[0030] Wherein, the corrosion-resistant lithium-philic layer is Ni-B, Ni-Sn, Ni-Zn, Ni-Ag or Ni-Graphite.
[0031] The present invention also discloses a method for preparing a micro-textured porous multi-layer structure composite current collector, comprising: using a porous polymer film as a template for the composite current collector, depositing chemically plated metal layers on both sides thereof, plating the chemically plated metal layer on the outside of the porous polymer film using a colloidal palladium or colloidal copper catalyst during deposition, and then using an electroplating method to prepare a micro-textured metal copper layer and a corrosion-resistant lithium-philic layer.
[0032] Example 1
[0033] This embodiment uses a PET porous polymer film with a thickness of 13μm, a pore size of 30μm and a porosity of 30% as a base film, firstly uses colloidal copper to realize its metallization, and deposits a 0.1μm chemically plated metal layer on its surface by chemical plating, then uses electroplating to prepare a micro-textured metal copper layer with a thickness of 0.8μm, and finally uses electroplating to prepare a Ni-B layer with a thickness of 0.1μm, and obtains a micro-textured porous multi-layer composite current collector with a thickness of 15μm, a pore size of 28μm, a porosity of 26.1%, and a particle size of 0.1μm of the convex texture. According to GB / T29847-2013, the tensile strength of the composite current collector is 225MPa; the elongation is 12.5%; and the resistivity is 15mΩ.
[0034] The preparation method of the composite current collector of this embodiment includes:
[0035] The membrane was impregnated with a 0.1 vol.% 3-aminopropyltrimethoxysilane acetone solution, and then heated at 125°C for 5 minutes to achieve high-temperature drying to form a siliceous layer. Furthermore, the impregnated and high-temperature dried surface-modified PET porous polymer membrane was irradiated with ultraviolet light of a wavelength of 254 nm for 1 minute.
[0036] The surface modified PET porous polymer membrane was activated with colloidal copper on the surface. The selected solutions were: CuCl2 (0.05 M / L), Na3C6H5O7 (0.1 M / L), DMAB (0.1 M / L) and H3BO3 (0.1 M / L). The pH was adjusted to 5 with NaOH. The activation was carried out for 10 min at room temperature.
[0037] The PET porous polymer film activated by colloidal copper was subjected to chemical copper plating. The plating solution was selected as follows: 10 g / L copper sulfate, 20 g / L potassium sodium tartrate, 10 g / L sodium hydroxide, and 10 mL / L formaldehyde. The sample was taken out after 2 minutes, washed and dried to obtain a porous polymer film with a chemically plated metal layer.
[0038] The porous polymer film with chemically plated metal layer was electroplated to obtain a micro-textured copper layer. The plating solution was selected as follows: copper sulfate 250g / L, sulfuric acid 50g / L, chloride ion 50ppm, sodium tungstate 30ppm, SH110 50ppm, temperature 40℃, cathode current density 2A / dm 2 , and after 1.5 minutes, a porous polymer membrane with a chemically plated metal layer and a micro-textured metal copper layer was obtained.
[0039] The Ni-B corrosion-resistant and lithium-philic layer was electroplated on a porous polymer film with an electroless metal layer and a micro-textured copper layer. The plating solution was selected as follows: nickel sulfate 250g / L, nickel chloride 40g / L, DMAB 5g / L, boric acid 5g / L, sodium dodecyl sulfate 0.1g / L, temperature 50℃, cathode current density 30g / L 5A / dm 2 , and take it out after 0.5 min to obtain the composite current collector.
[0040] from Figure 1 It can be seen that the composite current collector is composed of a porous polymer film, an electroless copper layer, a micro-textured copper layer and a corrosion-resistant lithium-philic layer. Figure 2 and Figure 3 It can be seen that the composite current collector has a large number of microscopic pore structures. Figure 4 It can be seen that the composite current collector prepared in this embodiment has a pore size of about 28 μm, a thickness of 15 μm, and a porosity of 26.1%. Figure 5 It can be seen that a layer of raised texture is attached to both the inner and outer surfaces of the pores of the composite current collector.
[0041] Example 2
[0042] This embodiment uses a PE porous polymer membrane with a thickness of 4μm, a pore size of 3.0μm and a porosity of 60% as a base membrane, firstly uses colloidal palladium to achieve metallization, and deposits a 0.1μm chemically plated metal layer on its surface by chemical plating, then uses electroplating to prepare a 0.4μm thick micro-textured metal copper layer, and finally uses electroplating to prepare a 0.1μm thick Ni-Graphite layer, and obtains a micro-textured porous multi-layer composite current collector with a thickness of 5.2μm, a pore size of 1.8μm, a porosity of 25%, and a particle size of 0.05μm of the convex texture. According to GB / T29847-2013, the tensile strength of the composite current collector is 310MPa; the elongation is 14.5%; and the resistivity is 19mΩ.
[0043] The preparation method of the composite current collector of this embodiment includes:
[0044] The PE porous polymer membrane was cleaned with sulfuric acid having a concentration of 4 wt. % to obtain a PE porous polymer membrane with a clean surface.
[0045] The surface of the PE porous polymer membrane that has been surface acid-washed is activated with colloidal palladium. The selected solutions are: SnCl2 1.5 g / L, HCl solution 6%, colloidal palladium 0.5%, treatment temperature 30°C, treatment time 1.0 min, and then 10% hydrochloric acid solution is used for degumming, the treatment temperature is 40°C, and the treatment time is 1.0 min, so that the palladium is exposed to become a catalytic active center.
[0046] The PE porous polymer membrane activated by colloidal palladium was subjected to chemical nickel plating. The plating solution was selected as follows: 30 g / L nickel chloride, 0.5 g / L sodium borohydride, 60 g / L ethylenediamine, 40 g / L sodium hydroxide, and 3 g / L sodium fluoride. The sample was taken out after 2 minutes, washed and dried to obtain a porous polymer membrane with a chemically plated metal layer.
[0047] The porous polymer film with chemically plated metal layer was electroplated with a micro-textured copper layer. The plating solution was selected as follows: copper sulfate 150g / L, sulfuric acid 100g / L, chloride ion 50ppm, sodium molybdate 30ppm, temperature 40°C, cathode current density 1A / dm 2 , and after 1.5 minutes, a porous polymer membrane with a chemically plated metal layer and a micro-textured metal copper layer was obtained.
[0048] The Ni-B corrosion-resistant lithium-philic layer was electroplated on the porous polymer film with chemically plated metal layer and micro-textured metal copper layer. The plating solution was selected as follows: nickel sulfate 250g / L, nickel chloride 40g / L, DMAB 5g / L, boric acid 30g / L, sodium dodecyl sulfate 0.1g / L, graphite 0.5g / L, temperature 50℃, cathode current density 5A / dm2 , and take it out after 0.5 min to obtain the composite current collector.
[0049] Example 3
[0050] This embodiment uses a PSF porous polymer membrane with a thickness of 10 μm, a pore size of 10 μm and a porosity of 50% as a base membrane, firstly uses colloidal palladium to achieve metallization, and deposits a 0.1 μm chemically plated metal layer on its surface by chemical plating, then uses electroplating to prepare a micro-textured metal copper layer with a thickness of 1.0 μm, and finally uses electroplating to prepare a Ni-Sn layer with a thickness of 0.1 μm, to obtain a micro-textured porous multi-layer composite current collector with a thickness of 12.4 μm, a pore size of 7.6 μm, a porosity of 30%, and a particle size of 0.1 μm of the convex texture. According to GB / T29847-2013, the tensile strength of the composite current collector is 276 MPa; the elongation is 13.5%; and the resistivity is 14 mΩ.
[0051] The preparation method of the composite current collector of this embodiment includes:
[0052] The PSF porous polymer membrane was cleaned with sulfuric acid having a concentration of 4 wt. %, thereby obtaining a PSF porous polymer membrane with a clean surface.
[0053] The acid-washed PSF porous polymer membrane was activated with colloidal palladium on its surface. The selected solution was: SnCl2 1.5 g / L, HCl solution 6%, colloidal palladium 0.5%, the treatment temperature was 35°C, and the treatment time was 1.5 min. Then, a 10% hydrochloric acid solution was used for debonding. The treatment temperature was 35°C and the treatment time was 1.5 min, so that the palladium was exposed to become the catalytic active center.
[0054] The PE porous polymer membrane activated by colloidal palladium was chemically plated with copper and nickel. The plating solution was selected as follows: 15 g / L copper sulfate, 60 g / L potassium sodium tartrate, 10 g / L sodium hydroxide, 4 g / L nickel chloride, and 15 mL / L formaldehyde. The sample was taken out after 2 minutes, washed and dried to obtain a porous polymer membrane with a chemically plated metal layer.
[0055] The electroplated copper layer is electroplated with the chemically plated metal layer and the micro-textured copper layer. The plating solution is selected as follows: 150 g / L copper sulfate, 100 g / L sulfuric acid, 50 ppm chloride ion, 30 ppm sodium molybdate, 50 ppm titanium sulfate, temperature 40 ° C, cathode current density 3.5 A / dm 2 , and after 3.0 min, a porous polymer membrane with a chemically plated metal layer and a micro-textured metal copper layer was obtained.
[0056] The Ni-Sn corrosion-resistant lithium-philic layer was electroplated on a porous polymer film with an electroless metal layer and a micro-textured copper layer. The plating solution was selected as follows: nickel sulfate 80 g / L, stannous chloride 10 g / L, DMAB, boric acid 30 g / L, sodium dodecyl sulfate 0.1 g / L, temperature 45 °C, cathode current density 5 A / dm 2 , and take it out after 1.0 min to obtain the composite current collector.
[0057] Example 4
[0058] This embodiment uses a PE porous polymer film with a thickness of 8μm, a pore size of 10μm and a porosity of 60% as a base film, firstly uses colloidal copper to realize its metallization, and deposits a 0.1μm chemically plated metal layer on its surface by chemical plating, then uses electroplating to prepare a micro-textured metal copper layer with a thickness of 0.4μm, and finally uses electroplating to prepare a Ni-Zn layer with a thickness of 0.2μm, and obtains a micro-textured porous multi-layer composite current collector with a thickness of 9.4μm, a pore size of 8.6μm, a porosity of 45%, and a particle size of 0.1μm of the convex texture. According to GB / T29847-2013, the tensile strength of the composite current collector is 210MPa; the elongation is 10.5%; and the resistivity is 20mΩ.
[0059] The preparation method of the composite current collector of this embodiment includes:
[0060] The membrane was impregnated with a 0.1 vol.% 3-aminopropyltrimethoxysilane acetone solution, and then heated at 125°C for 5 minutes to achieve high-temperature drying to form a siliceous layer. Furthermore, the surface-modified PE porous polymer membrane that had been impregnated and high-temperature dried was irradiated with ultraviolet light at a wavelength of 254 nm for 1 minute.
[0061] The surface modified PE porous polymer membrane was activated with colloidal copper on the surface, and the selected solutions were: CuCl2 (0.05M / L), Na3C6H5O7 (0.1M / L), DMAB (0.1M / L) and H3BO3 (0.1M / L), and the pH was adjusted to 5 with NaOH. The activation was carried out for 10 minutes at room temperature.
[0062] The porous polymer film activated by surface colloidal copper was subjected to chemical copper plating. The plating solution was selected as follows: 15 g / L copper sulfate, 30 g / L potassium sodium tartrate, 15 g / L sodium hydroxide, and 15 mL / L formaldehyde. The sample was taken out after 1.5 minutes, washed and dried to obtain a porous polymer film with a chemically plated metal layer.
[0063] The porous polymer film with chemically plated metal layer was electroplated with a micro-textured copper layer. The plating solution was selected as follows: copper sulfate 250g / L, sulfuric acid 50g / L, chloride ion 50ppm, collagen 20ppm, SPS 50ppm, temperature 40℃, cathode current density 5A / dm 2 , and after 1.0 min, a porous polymer membrane with a chemically plated metal layer and a micro-textured metal copper layer was obtained.
[0064] A Ni-Zn corrosion-resistant lithium-philic layer was electroplated on a porous polymer film having an electroless metal layer and a micro-textured copper layer. The plating solution was selected as follows: 150 g / L nickel sulfate, 50 g / L zinc sulfate; 20 g / L ammonium sulfate, 50 g / L sodium sulfate, 20 g / L boric acid, 0.1 g / L sodium dodecyl sulfate, pH 3, temperature 50 °C, cathode current density 5 A / dm 2 , and take it out after 0.5 min to obtain the composite current collector.
[0065] Comparative Example 1
[0066] In this comparative example, a PET polymer film with a thickness of 13 μm and no openings is used as a base film. First, colloidal palladium is used to achieve metallization, and then a 0.1 μm chemically plated metal copper layer is deposited on its surface by chemical plating, and a metal copper layer with a thickness of 0.9 μm is prepared by electroplating to obtain a composite copper foil current collector.
[0067] The method for preparing the current collector of this embodiment includes:
[0068] The PE porous polymer membrane was cleaned with sulfuric acid having a concentration of 4 wt. % to obtain a PE porous polymer membrane with a clean surface.
[0069] The surface of the PE porous polymer membrane that has been surface acid-washed is activated with colloidal palladium. The selected solutions are: SnCl2 1.5 g / L, HCl solution 6%, colloidal palladium 0.5%, treatment temperature 30°C, treatment time 1.0 min, and then 10% hydrochloric acid solution is used for degumming, the treatment temperature is 40°C, and the treatment time is 1.0 min, so that the palladium is exposed to become a catalytic active center.
[0070] The PE porous polymer membrane activated by colloidal copper was subjected to chemical copper plating. The plating solution was selected as follows: 15 g / L copper sulfate, 30 g / L potassium sodium tartrate, 15 g / L sodium hydroxide, and 15 mL / L formaldehyde. The sample was taken out after 1.5 minutes, washed and dried to obtain a porous polymer membrane with a chemically plated metal copper layer.
[0071] The porous polymer film with chemically plated copper layer was electroplated with copper layer, and the plating solution was selected as follows: copper sulfate 150g / L, sulfuric acid 100g / L, chloride ion 50ppm, SPS 50ppm, collagen 30ppm, HEC 50ppm, temperature 40℃, cathode current density 4A / dm 2 , and after 1.5 minutes, take it out to obtain the composite copper foil current collector.
[0072] Comparative Example 2
[0073] In this embodiment, a titanium cathode is selected as the substrate, and an electrolytic copper foil with a thickness of 8 μm is prepared by electroplating.
[0074] The method for preparing the electrolytic copper foil of this embodiment comprises:
[0075] The titanium cathode is ground and polished with sandpaper of no less than 1500 mesh to obtain a smooth titanium surface. The copper layer is electroplated on the titanium cathode, and the plating solution is selected as follows: copper sulfate 80g / L, sulfuric acid 180g / L, chloride ion 50ppm, SPS 30ppm, collagen 20ppm, HEC 80ppm, temperature 55℃, cathode current density 20A / dm 2 After 3.0 min, the electrolytic copper foil was taken out and peeled off.
[0076] Table 1
[0077]
[0078]
[0079] Note: The more ★, the better the performance. Among them, GB / T29847-2013 tests the mass per unit area; YY / T1154-2009 tests the surface area; GB / T 24196-2009 tests the corrosion resistance; and JY / T 0584-2020 tests whether it is lithium-philic.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A micro-textured porous multi-layer composite current collector, characterized in that: include: A porous polymer film in the middle, chemically plated metal layers on both sides of the porous polymer film, micro-textured metal copper layers on the outsides of the two chemically plated metal layers, and corrosion-resistant lithium-philic layers on the outsides of the two micro-textured metal copper layers; The two chemically plated metal layers, the micro-textured metal copper layer, and the corrosion-resistant lithium-philic layer are uniformly deposited on the inner surface and the outer surface of the pores of the porous polymer membrane in sequence; The porous polymer film has a thickness of 4 to 13 μm, a pore size of 3 to 30 μm, and a porosity of 30 to 60%. The composite current collector has a thickness of 5.2 to 15 μm, a pore size of 1.7 to 28 μm, and a porosity of 25 to 45%. The composite current collector has protruding textures attached to the inner and outer surfaces of the holes; the particle size of the protruding textures is 0.05-0.1 μm; The composite current collector has a tensile strength of ≥200 MPa, an elongation of ≥10%, and a resistivity of ≤20 mΩ.
2. The micro-textured porous multi-layer composite current collector according to claim 1, characterized in that: The porous polymer film is a PET film, a PE film, a PP film or a PSF film.
3. The micro-textured porous multi-layer composite current collector according to claim 1, characterized in that: The chemically plated metal layer is a copper, nickel or copper-nickel layer.
4. The micro-textured porous multi-layer composite current collector according to claim 1, characterized in that: The corrosion-resistant lithium-philic layer is Ni-B, Ni-Sn, Ni-Zn, Ni-Ag or Ni-Graphite.
5. A method for preparing a micro-textured porous multi-layer composite current collector, characterized in that: include: A porous polymer membrane is used as a template for a composite current collector, and chemically plated metal layers are deposited on both sides thereof. During the deposition, a chemically plated metal layer is plated on the outside of the porous polymer membrane using a colloidal palladium or colloidal copper catalyst, and then a micro-textured metal copper layer and a corrosion-resistant lithium-philic layer are prepared by an electroplating method.
Citation Information
Cited By
Negative electrode current collector for solid-state battery, preparation method of negative electrode current collector and negative electrode for solid-state battery
CN121149254A